Associations between sports participation and psychological difficulties during childhood: A two-year follow up. Issue 3 (May 2015) - Vella, Stewart A.; Cliff, Dylan P.; Magee, Christopher A.; Okely, Anthony D.
Abstract Objectives This paper assessed the associations between sports participation and the development of psychological strengths and difficulties during childhood. Design Two-year follow up study of a sample of 4042 Australian children who were followed from age 8 years to 10 years. Methods Parents reported children's participation in organised sports, and completed the Strengths and Difficulties Questionnaire. Univariate general linear models were used to examine the association between changes in sports participation and psychological strengths and difficulties at 10 years, adjusting for psychological strengths and difficulties at age 8. Results Children who maintained participation in sport had lower rates of parent-reported psychological difficulties at 10 years compared with children who dropped out of sport. Less internalising problems were also reported for children who participated in organised sports compared to children who dropped out of sports and children who did not participate in sports. These relationships did not differ by BMI, socioeconomic status, or parental education. Conclusions Greater psychological difficulties are experienced by children who drop out of sports, and greater social and emotional problems are experienced by children who drop out of sports and who do not participate in organised sports. Due consideration should be given to the quality and implementation of sporting programs to ensure that they provide benefits to mental health. Due consideration should also be given to the potential psychological difficulties being experienced by children who drop out of organised sports as a higher level of psychological difficulties may be experienced prior to or subsequent to dropout.